When Vessels and Sarcomas Combine: A Review of the Inferior Vena Cava Leiomyosarcoma - João Martins Gama; Rui Almeida; Rui Caetano Oliveira; José Casanova (Journal of Vascular Diseases, 2024)
Leiomyosarcomas (LMSs) are malignant neoplasms of soft muscle differentiation that can be classified into five distinct groups according to site-related origin: intra-abdominal, subcutaneous or deep soft tissue of the limbs, cutaneous, external genitalia, and vascular. This distinction reflects different biological behaviors as well as molecular changes, thus reflecting different prognoses and therapeutic options. Vascular LMSs are the least frequent, arising from the walls of the blood vessels, most commonly from the inferior vena cava. Due to its deep location, symptoms are non-specific, and the disease presents at an advanced stage, sometimes with metastases. Surgery is the treatment of choice, associated with chemo- and radiotherapy. Due to its rarity, most departments have minimal experience handling this disease. This article reviews the current knowledge on vascular leiomyosarcomas, particularly the inferior vena cava leiomyosarcoma.